2013
DOI: 10.1186/1475-2859-12-116
|View full text |Cite
|
Sign up to set email alerts
|

Trace element associated reduction of norleucine and norvaline accumulation during oxygen limitation in a recombinant Escherichia coli fermentation

Abstract: BackgroundNorleucine and norvaline belong to a group of non-canonical amino acids which are synthesized as byproducts in the branched chain amino acid metabolism of Escherichia coli. The earlier observed misincorporation of these rare amino acids into recombinant proteins has attracted increasing attention due to the rising use of protein based biopharmaceuticals in clinical application. Experimental data revealed pyruvate overflow inducing conditions, which typically occur in oxygen limited zones of large-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Zhang et al reported a relationship between Mo and Se utilization in prokaryotes [64]. Furthermore, both Se and Mo play a similar role in a recombinant Escherichia coli fermentation [65]. Based on the studies mentioned above, our study further indicated a close association between Se and Mo excretion, and the association might even exist in their metabolism and physiological function in human beings.…”
Section: Discussionsupporting
confidence: 68%
“…Zhang et al reported a relationship between Mo and Se utilization in prokaryotes [64]. Furthermore, both Se and Mo play a similar role in a recombinant Escherichia coli fermentation [65]. Based on the studies mentioned above, our study further indicated a close association between Se and Mo excretion, and the association might even exist in their metabolism and physiological function in human beings.…”
Section: Discussionsupporting
confidence: 68%
“…While several previous studies have focused on the impact of oxygen availability on E. coli , only a few have studied the relevance of this parameter on product quality. For example, it has been demonstrated that oxygen limitation contributes to the synthesis of the non-canonical amino acid norvaline by E. coli [ 21 , 22 ]. This may affect the quality of the recombinant protein produced.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of norleucine incorporation in the recombinant protein during an E. coli fermentation depends on the nature of the recombinant protein being produced and the fermentation process (e.g., medium composition, process parameters such as pH, temperature, etc.) . When methionine was not fed during the fermentation, the recombinant proteins produced in the AF1, AF2, and AF3 fermentation processes accumulated 0.7–10% of norleucine in place of methionine residues (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The extent of norleucine incorporation in the recombinant protein during an E. coli fermentation depends on the nature of the recombinant protein being produced and the fermentation process (e.g., medium composition, process parameters such as pH, temperature, etc.). 19 When methionine was not fed during the fermentation, the recombinant proteins produced in the AF1, AF2, and AF3 fermentation processes accumulated 0.7-10% of norleucine in place of methionine residues ( Table 4). Contrary to the previous observations, 3,20 these results indicate that the norleucine incorporation is not random, as some positions had higher levels of norleucine incorporation than others in recombinant proteins produced in all three processes ( Table 4).…”
Section: Norleucine Incorporation During E Coli Fermentationsmentioning
confidence: 99%